2020
DOI: 10.3390/ijerph17228471
|View full text |Cite
|
Sign up to set email alerts
|

Association between Intention to Quit Cigarette Smoking and Use of Heated Tobacco Products: Application of Smoking Intensity Perspective on Heated Tobacco Product Users

Abstract: Tobacco companies have designed sophisticated marketing strategies for heated tobacco products (HTPs), and many smokers are exposed to advertisements purporting that HTPs can replace combustible cigarettes. The present study evaluates the relationship between poly-use of tobacco products and intention to quit cigarette smoking in association with smoking intensity, a meaningful indication of one’s interest in quitting cigarette smoking. A total of 36,397 current cigarette smokers who participated in the 2019 K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
2
6
1
Order By: Relevance
“…This result might be reasonable because dual users needed to quit both cigarette smoking and HTPs, which could be more difficult than quitting individually. Moreover, this result was consistent with the report from Ryu et al that dual users of cigarettes and HTPs had a lower intention to quit smoking within one month than exclusively cigarette smokers 21 . Furthermore, dual users might have a different clinical profile that could attenuate smoking cessation success compared to exclusively cigarette or exclusively HTP users.…”
Section: Discussionsupporting
confidence: 92%
“…This result might be reasonable because dual users needed to quit both cigarette smoking and HTPs, which could be more difficult than quitting individually. Moreover, this result was consistent with the report from Ryu et al that dual users of cigarettes and HTPs had a lower intention to quit smoking within one month than exclusively cigarette smokers 21 . Furthermore, dual users might have a different clinical profile that could attenuate smoking cessation success compared to exclusively cigarette or exclusively HTP users.…”
Section: Discussionsupporting
confidence: 92%
“…This result might be reasonable because dual users needed to quit both cigarette smoking and HTPs, which could be more difficult than quitting individually. Moreover, this result was consistent with the report from Ryu et al that dual users of cigarettes and HTPs had a lower intention to quit smoking within 1 month than exclusively cigarette smokers 22. Furthermore, dual users might have a different clinical profile that could attenuate smoking cessation success compared with exclusively cigarette or exclusively HTP users.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, this result was consistent with the report from Ryu et al that dual users of cigarettes and HTPs had a lower intention to quit smoking within 1 month than exclusively cigarette smokers. 22 Furthermore, dual users might have a different clinical profile that could attenuate smoking cessation success compared with exclusively cigarette or exclusively HTP users. Our study indicated that dual users were younger and had shorter smoking duration than exclusively cigarette smokers.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, more HTP smokers reported that HTPs were helpful in quitting smoking than nonsmokers; this trend was greater in dual users of HTPs and CCs and triple users or HTPs, liquid e-cigarettes, and CCs [ 12 ]. However, in several other studies, no significant difference in smoking cessation intentions or success rates were noted between HTP use and non-use [ 3 , 13 , 14 ]. A recent study examining all smoking cessation attempts using CCs, HTPs, and liquid e-cigarettes among Korean adults showed that the rates of future cessation intention and experience attempting smoking cessation were significantly lower in HTP versus CC smokers [ 15 ].…”
Section: Introductionmentioning
confidence: 93%